High-Power Microwave Antennas: A Comprehensive Review - Mashrur Zawad; Sohel Rana; Travis D. Fields; Anthony N. Caruso; Kalyan C. Durbhakula; Mohamed Z. M. Hamdalla (IEEE Access)
High-power antennas have emerged as a critical area of focus for researchers in recent design efforts, particularly for high-power microwave (HPM) technologies. The increasing demand for gigawatt power handling microwave systems in directed energy and electronic warfare applications necessitates the integration of innovative high-power design strategies into traditional antenna design procedures, where the emphasis is on developing wideband and high-gain antennas. Owing to the lack of a comprehensive study of recently proposed antennas for high-power applications, this review paper provides an in-depth discussion, comparison, and examination of the latest advancements in HPM antenna technology. In addition, this review provides a qualitative and quantitative assessment of HPM antennas using widely used antenna metrics such as the center frequency, electrical size, bandwidth, peak gain, and power handling capability. Moreover, this review provides a comprehensive overview of the methodology employed in designing high-power microwave antennas and discusses the outcomes obtained. In addition, the employment of special types of gases, low-loss dielectric materials, and smoothly varying structures to minimize charge buildups, air breakdown, and arching has proven to help improve power handling capability. Using the quantitative antenna metric information published in the open literature, we compiled a table showing performance comparisons between various antenna types and created figures depicting inter- and intra-antenna relationships and tradeoffs. Among the various HPM antennas, the horn antenna can be determined as a versatile and state-of-the-art HPM antenna element demonstrating 10s – 100s of megawatts (MWs) of peak power per element, narrow-to-ultrawideband operating bandwidth, small-to-large electrical size, and medium-to-high gain values. Antennas such as the cavity, impulse radiating, leaky-wave, reflectarray, and other array antennas have achieved state-of-the-art high peak power performance with a tradeoff between electrical size, gain, and bandwidth. In conclusion, this paper revisits HPM antenna designs, highlights noticeable challenges for HPM antenna researchers and engineers, suggests future research directions, and summarizes the key outcomes.